2019
DOI: 10.1177/1069072719825777
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Calling in a Social Cognitive Model of Well-Being

Abstract: The present study examined the role of calling in a social cognitive model of well-being using a sample of 328 South Korean teachers. The model incorporating calling into the social cognitive model of well-being demonstrated an excellent fit, and our variables accounted for significant variance in job satisfaction (47%) and life satisfaction (38%). Among the 12 direct paths of the proposed model, 10 hypothesized paths were significant. The direct paths from positive affect to calling, self-efficacy, job satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
(131 reference statements)
0
10
0
1
Order By: Relevance
“…Prior empirical studies also showed some contradictory results. For instance, work meaning and job satisfaction have been posited as typical consequences of developing a calling (e.g., Duffy et al, 2018 ; Lee et al, 2020 ). Some scholars also explored whether the search for calling is associated with work meaning and job satisfaction.…”
Section: The Outcomes Of Searching For Callingmentioning
confidence: 99%
“…Prior empirical studies also showed some contradictory results. For instance, work meaning and job satisfaction have been posited as typical consequences of developing a calling (e.g., Duffy et al, 2018 ; Lee et al, 2020 ). Some scholars also explored whether the search for calling is associated with work meaning and job satisfaction.…”
Section: The Outcomes Of Searching For Callingmentioning
confidence: 99%
“…Career goal self-efficacy (CGSE) is one of the critical components of sustainable career development ( Allan and Duffy, 2014 ). When college students inevitably encounter various difficulties during their study and personal growth periods, such as a low level of gratitude ( Wu, 2020 ), lack of environmental and meaning in life exploration ( Su et al, 2014 ), and lack of necessary occupational skills in the critical stages of determining career development goals ( Wang and Gao, 2013 ), it is required to analyze their inner characteristics and drive their career calling to enhance CGSE ( Allan and Duffy, 2014 ; Lee et al, 2020 ). An individual’s internal CGSE shows a positive attitude which can help individuals to enhance their confidence in their inner resources and recognition to be a teacher ( Zhang et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Against this backdrop, there has been a growing interest in "occupational callings" (Duffy, Dik, Douglass, England, & Velez, 2018), defined as "an approach to work that reflects seeking a sense of overall purpose and meaning and is used to help others or contribute to the common good, motivated by an external or internal summons" (Duffy et al, 2018, p. 426). Despite the dominant emphasis on the positive aspects of seeing work as a calling, as a form of obtaining life satisfaction and career commitment (H. S. Lee, E. S. Lee, & Shin, 2020), many studies on the topic explore a different perspective. For example, Lysova, Jansen, Khapova, Plomp, and Tims (2018) and Silva, Felix, and Mainardes (2021) have explored the challenges individuals face while trying to live callings, considering that some people are unable to build a career with these characteristics.…”
Section: Introductionmentioning
confidence: 99%